Hubungan Karakteristik Individu Dengan Perilaku Mencuci Tangan Sebagai Upaya Pencegahan COVID-19 Pada Dewasa Muda di Kota Pekanbaru - Tyagita Widya Sari; Cindy Herwiti (Jurnal Ilmu Kesehatan Abdurrab, 2023)
Coronavirus Disease 2019 (COVID-19) is a disease that has never been previously identified in humans. The case is increasingly acclaimed on a daily basis around the world, including in Indonesia. At the Riau Province level, 31,397 confirmed cases of COVID-19 have been reported from 12 districts/cities on February 28, 2021 and the Pekanbaru city is the most abundant COVID-19 case report in the Riau province. By the increasing number of cases of COVID-19, The Indonesian government is socializing one of the measures to prevent the transmission of COVID-19 which is in accordance with WHO recommendations, namely by washing hands using soap and running water or using hand sanitizer. However, some people in Indonesia still consider hand washing behavior as an ordinary recommendation so there are still many people who do not apply hand washing behavior. Meanwhile shand washing behavior violations are mainly made by a group of young adults who are 18 to 25 years of age. The objective of this study was to determine the correlation of individual characteristics and hand washing behavior as COVID-19 prevention effort on young adults in Pekanbaru City 2021. This research used an analytic observational with a cross sectional study design. This research was conducted on a population of young adults in Pekanbaru City on June 2021. The sampling technique was carried out by cluster sampling with a sample size of 440 respondents. Data analysis was conducted through chi square's test and spearman's correlation test for p-value and coefficient correlation (r). There was a significant correlation between gender (p-value = 0.022) and hand washing behavior. However, there were no significant correlation between latest education level (p-value = 0.213) and employment status (p-value = 0.118) and hand washing behavior. The individual characteristics which was correlate with hand washing behavior is gender, while latest education level and employment status have no correlation with hand washing behavior as COVID-19 prevention effort on young adults in Pekanbaru City 2021.